A design of experiments (DoE) approach to identify the influencing parameters that determine poly-D,L-lactic acid (PDLLA) electrospun scaffold morphologies - Ruiter, Floor Agnes Andrea; Alexander, Cameron; Rose, Felicity R.A.J.; Segal, Joel (IOP Publishing, 2017)
Electrospun fibrous materials have increasing applications in regenerative medicine due to the similarity of fibre constructs to the morphology of certain extracellular matrices. Although experimentally the electrospinning method is relatively simple, at the theoretical level the interactions between process parameters and their influence on the fibre morphology is not yet fully understood. Here, we hypothesised that a design of experiments (DoE) model could determine combinations of process parameters that result in significant effects on poly-D,L-lactic acid (PDLLA) fibre morphology. The process parameters used in this study were applied voltage, needle-to-collector distance, flow rate and polymer concentration. Data obtained for mean fibre diameter, standard deviation of the fibre diameter (stdev, measure of fibre morphology) and presence of 'beading' on the fibres (beads per µm2) were evaluated as a measure of PDLLA fibre morphology. Uniform fibres occurred at standard deviations of ≤ 500 nm, 'beads-on-string' morphologies were apparent between ± 500-1300 nm and large beads were observed at ± 1300-1800 nm respectively. Mean fibre diameter was significantly influenced by the applied voltage and interaction between flow rate and polymer concentration. Fibre morphology was mainly influenced by the polymer concentration, while bead distribution was significantly influenced by the polymer concentration as well as the flow rate. The resultant DoE model regression equations were tested and considered suitable for the prediction of parameters combinations needed for desired PDLLA fibre diameter and additionally provided information regarding the expected fibre morphology.